2022
DOI: 10.1021/acs.energyfuels.2c02799
|View full text |Cite
|
Sign up to set email alerts
|

Selective Growth of Molybdenum Sulfo-Selenides on a Defect-Rich Carbon Nanotube Skeleton for Efficient Energy Storage and Hydrogen Generation Applications

Abstract: The design of multifunctional advanced nanomaterials is a fascinating and demanding approach to harness clean and sustainable energy. Two-dimensional metallic transition-metal chalcogenide-based alloys are regarded as a viable option for energy storage and hydrogen evolution reaction (HER) applications due to their improved electrical conductivity, presence of additional active sites, and capacity to make hybrids with various materials. Herein, a facile hydrothermal approach is employed to construct 1D/2D MoSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…5b) respectively. 63,64 Similarly, the Se 3d spectrum of the MoSSe@RGO nanocomposite (Fig. 5c), displays two peaks at 53.7 and 54.7 eV corresponding to Se 2− 3d 5/2 and Se 2− 3d 3/2 , respectively.…”
Section: Resultsmentioning
confidence: 90%
“…5b) respectively. 63,64 Similarly, the Se 3d spectrum of the MoSSe@RGO nanocomposite (Fig. 5c), displays two peaks at 53.7 and 54.7 eV corresponding to Se 2− 3d 5/2 and Se 2− 3d 3/2 , respectively.…”
Section: Resultsmentioning
confidence: 90%
“…In one of our previous works, we analyzed and established the electrochemical performance of MoSSe/CNT. [ 53 ] We are not repeating the detailed material characterization and electrochemical assessment of MoSSe/CNT but for a quick reference, we have provided the XRD pattern and FESEM images of MoSSe/CNT in Figure S8 and S9, Supporting Information, to establish the purity and morphology of the negative electrode. Also, the basic three‐electrode analysis of the MoSSe/CNT with the long cyclic study is provided in Figure S10, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…130,131 Studies across the globe revealed that a hybrid formation of these pristine electrode materials can overcome many of these deciencies. [132][133][134] One of the well-established hybrid formations is pseudocapacitor/EDLC hybrids. 128,135,136 In these hybrid electrodes, the overall performance of the supercapacitor benets from the individual advantages of both of these materials through a synergistic interaction.…”
Section: Magnetic Eld Effects In Pseudocapacitor/edlc Hybrid Electrodesmentioning
confidence: 99%
“…128,135,136 In these hybrid electrodes, the overall performance of the supercapacitor benets from the individual advantages of both of these materials through a synergistic interaction. 133,[137][138][139][140][141] Due to the presence of different electrochemical storage systems, magnetic eld effects in pseudocapacitor/EDLC hybrids need to be studied separately.…”
Section: Magnetic Eld Effects In Pseudocapacitor/edlc Hybrid Electrodesmentioning
confidence: 99%